Snow white and the seven dwarfs (England : Usborne publication, 2005)
Each book in this series is designed to encourage independent reading and covers a range of subject matter, including the retelling of children's classics, fairytales, and a wide variety of narrative non-fiction. This edition retells the Brothers Grimm story of 'Snow White'. Three titles in the popular Young Reading series are re-issued with hardback covers with audio CDs inserted into a wallet inside the back cover, making the book and CD easy to store together. The Young Reading series is developed with reading expert Alison Kelly from Roehampton University to help young readers grow in confidence and ability
"Snow White and the Seven Dwarfs" is a classic fairy tale about a beautiful princess who is forced to flee from her jealous stepmother, the Evil Queen. She finds refuge with seven dwarfs in their cottage until the Queen's wicked plot puts her in danger, ultimately leading to a happy ending. Location: 3A
Keywords: Snow white